World development indicators (1998) The world bank (Washington, D.C. : International Bank for Reconstruction and Development/The World Bank, 1997)
"Grouped under six headings--world view, people, environment, economy, states and markets, and global links--the data provide a comprehensive statistical survey of world development"--User's Manual.
Description based on: 1998; title from disc label.
Keywords: Economic development -- Statistics -- Periodicals; Economic indicators -- Periodicals; Social indicators -- Periodicals